Egyptology search for the tomb of Osiris, being the journal of Miss Emily Sands, November 1926- - Steer, Dugald (Templar Publishing, 2004)
Purports to be the journal of Emily Sands during her travels in Egypt in 1926 to find the lost tomb of Osiris. Based on real Egyptology, each chapter covers a different place in Egypt.